Differential anti-thrombotic benefit and bleeding risk profiles of antagonists of protease-activated receptor 1 and 4 in Cynomolgus Macaques. Issue 145 (September 2016) - Wickham, L. Alexandra; Sitko, Gary; Stranieri-Michener, Maria; Handt, Larry; Basso, Andrea; Fried, Steven; Chu, Lin; Maderia, Maria; Owens, Karen; Castriota, Gino; Chen, Zhu; Metzger, Joseph M.; et al.
Abstract: Platelet activation plays a crucial role in hemostasis and thrombosis. Thrombin, the most potent stimulus of platelet activation, mediates platelet activation via the protease activated receptors (PARs). The platelet PAR repertoire in mediating thrombin's action differs across species. Only nonhuman primate (NHP) platelet activation is known to be similar to humans, mediated by PAR1 and PAR4, hence limiting translational in vivo studies of PAR's role in thrombosis and hemostasis to NHPs. Earlier studies have demonstrated a range of distinct in vitro activities of PAR1 and 4 in platelet activation yet the implications of these events in vivo is unclear. The objective of this study is to investigate and compare the roles of PAR1 and PAR4 in hemostasis and thrombosis in a relevant animal species. NHP models for pharmacokinetic, ex vivo platelet aggregation responses, FeCI3 injury-mediated arterial thrombosis and template bleeding were developed in Cynomolgus Macaques. Potent and selective small molecule antagonists of PAR1 and PAR4 were characterized in an array of in vitro assays, and subsequently examined head-to-head in the NHP models. Treatment of NHPs with antagonists of PAR1 or PAR4 both resulted in strong inhibition of ex vivo platelet aggregation. At doses that led to similar inhibition of platelet aggregation, animals treated with the PAR4 antagonist showed similar levels of anti-thrombotic efficacy, but longer bleeding times, compared to animals treated with the PAR1 antagonist. These findings suggest that PAR1 antagonism will likely produce a larger therapeutic index (ie. a larger anti-thrombotic efficacy over bleeding risk margin) than PAR4 antagonism. Highlights: Antagonism of PAR1 and PAR4 resulted in similar anti-thrombotic efficacy. Antagonism of PAR4 but not PAR1 increased template bleeding time. Antagonism of PAR1 will likely produce a superior therapeutic index (efficacy vs bleeding risk) over antagonism of PAR4.